Freshbite / Siti Khadijah Hussain - Hussain, Siti Khadijah (Universiti Teknologi MARA, Kedah, 2024)
“Freshbite” is an innovative multifunctional planting product designed to enhance the convenience and accessibility of fresh vegetables in office environments. Featuring an ergonomic handle and a built-in stand, “Freshbite” seamlessly integrates into any office pantry. Its unique design allows employees to effortlessly pick fresh vegetables, promoting healthier eating habits and contributing to overall well-being. “Freshbite” not only serves as a practical tool for urban gardening but also as a stylish and functional addition to the modern workspace, encouraging a more sustainable and health-conscious lifestyle among office workers.